2018
DOI: 10.1002/adfm.201707221
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Double‐Slope Nonideality in Organic Field‐Effect Transistors

Abstract: The field effect transistor (FET) is arguably one of the most important circuit elements in modern electronics. Recently, a need has developed for flexible electronics in a variety of emerging applications. Examples include form‐fitting healthcare‐monitoring devices, flexible displays, and flexible radio frequency identification tags. Organic FETs (OFETs) are viable candidates for producing such flexible devices because they incorporate semiconducting π‐conjugated materials, including small molecules and conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 213 publications
1
84
1
Order By: Relevance
“…There are however side effects of the use of dopant additives, such as increases in the OFF‐state current and the undesirable diffusion of dopant molecules in the presence of an electric field or thermal energy, which has motivated the testing of nondopant additives. Phan et al blended fullerene (C 60 ) derivatives into donor‐acceptor p‐type polymer semiconductors, and observed that the presence of this additive suppresses bias stress instability: the blending of [6,6]‐phenyl‐C61‐butyric acid methyl ester (PC 61 BM) into poly[4‐(4,4‐dihexadecyl‐4H‐cyclopenta[1,2‐b:5,4‐b']dithiophen‐2‐yl)‐ alt ‐[1,2,5]thiadiazolo[3,4‐c]pyridine] (PCDTPT) had the effect that the first and 20th scan transfer curves are identical ( Figure b) . In other words, the bias stress–induced change in μ FET was significantly suppressed (Figure c).…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
See 1 more Smart Citation
“…There are however side effects of the use of dopant additives, such as increases in the OFF‐state current and the undesirable diffusion of dopant molecules in the presence of an electric field or thermal energy, which has motivated the testing of nondopant additives. Phan et al blended fullerene (C 60 ) derivatives into donor‐acceptor p‐type polymer semiconductors, and observed that the presence of this additive suppresses bias stress instability: the blending of [6,6]‐phenyl‐C61‐butyric acid methyl ester (PC 61 BM) into poly[4‐(4,4‐dihexadecyl‐4H‐cyclopenta[1,2‐b:5,4‐b']dithiophen‐2‐yl)‐ alt ‐[1,2,5]thiadiazolo[3,4‐c]pyridine] (PCDTPT) had the effect that the first and 20th scan transfer curves are identical ( Figure b) . In other words, the bias stress–induced change in μ FET was significantly suppressed (Figure c).…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…c) Multiple scans of FET mobility with PC 61 BM blend and without with PC 61 BM blend, as a function of gate bias. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…This phenomenon, also called double slope—high slope at low gate bias, but small slope at high gate bias in the transfer curves, has been commonly observed in high‐mobility OFETs . It has been attributed to different causes, such as contact resistance and charge trapping, based on studies on different molecular systems and device structures . However, there is still no general mechanism that is applicable to all molecular systems (e.g., p‐type and n‐type semiconductors) and device structures (e.g., thin films and single crystals).…”
Section: Reduction Potentials Absorption and Frontier Molecular Orbmentioning
confidence: 99%
“…It has been attributed to different causes, such as contact resistance and charge trapping, based on studies on different molecular systems and device structures . However, there is still no general mechanism that is applicable to all molecular systems (e.g., p‐type and n‐type semiconductors) and device structures (e.g., thin films and single crystals). To handle this problem, we used two ways to extract the field effect mobility from the transfer I – V curves.…”
Section: Reduction Potentials Absorption and Frontier Molecular Orbmentioning
confidence: 99%
“…The first aspect to be considered refers to a circumstance occurred in the recent years, known as the “mobility hype.” In the past years, an increasing number of works have reported mobility values exceeding 10 cm 2 V −1 s −1 for organic semiconductors, measured through OFET structures and extracted using the gradual channel approximation (GCA) model, the validity of which has later become argument of discussion. In particular, a number of authors have debated the correctness of the use of such extraction method in actual instances where some of the highest mobility values were measured, identifying a certain number of recurring patterns in the data and in the extraction methods that substantially invalidate an important number of high mobility claims . In practice, the validity of the GCA can be compromised owing to poor charge injection into the semiconductor and to the dependence of charge injection on the voltage applied to the electrodes.…”
Section: Open Challenges In the Route To Ghz Organic Fetsmentioning
confidence: 99%